2006
DOI: 10.1007/s11538-006-9104-x
|View full text |Cite
|
Sign up to set email alerts
|

On the Population Dynamics of the Malaria Vector

Abstract: A deterministic differential equation model for the population dynamics of the human malaria vector is derived and studied. Conditions for the existence and stability of a non-zero steady state vector population density are derived. These reveal that a threshold parameter, the vectorial basic reproduction number, exist and the vector can established itself in the community if and only if this parameter exceeds unity. When a non-zero steady state population density exists, it can be stable but it can also be dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 20 publications
(19 reference statements)
0
54
0
Order By: Relevance
“…The forms M B L and M B S are the Verhulst-Pearl logistic (Abdelrazec et al 2014;Ngwa 2005) and Maynard-Smith-Slatkin (Brannstrom and Sumpter 2005) oviposition functions, respectively. It should be mentioned that, in the form B L , the non-negativity condition on B(M) will only hold if M < K (hence, K is assumed to be greater than M).…”
Section: F L (T R)mentioning
confidence: 99%
“…The forms M B L and M B S are the Verhulst-Pearl logistic (Abdelrazec et al 2014;Ngwa 2005) and Maynard-Smith-Slatkin (Brannstrom and Sumpter 2005) oviposition functions, respectively. It should be mentioned that, in the form B L , the non-negativity condition on B(M) will only hold if M < K (hence, K is assumed to be greater than M).…”
Section: F L (T R)mentioning
confidence: 99%
“…Subsequent contributions have been made to extend the Ross-Macdonald malaria models considering age structure in the human population (Aron and May, 1982;Dietz, 1988;Anderson and May, 1991), acquired immunity (Aron and May, 1982;Aron, 1988), latency (Koella, 1991;Lopez et al, 2002;Koella and Antia, 2003;Koella and Boëte, 2003), spatial heterogeneity (Dye and Hasibeder, 1986;Hasibeder and Dye, 1988;Gupta and Hill, 1995;Gupta et al, 1994;Torres-Sorando and Rodriguez, 1997;Rodriguez and Torres-Sorando, 2001), individual-based models , habitat-based models (Gu and Novak, 2005), integrated models (McKenzie and Bossert, 2005), among other aspects (Bailey, 1982;Chitnis et al, 2006;Gu et al, 2003b;Killeen et al, 2000;McKenzie, 2000;Ngwa, 2006;Smith et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%
“…As malaria is one of the most serious health problems facing the world today, several studies have been made in an attempt to understand its dynamics and predict what may happen and then suggest strategies to eliminate it [3,8,10,12,15,21,22]. In this paper, a deterministic model (SIS for humans and SI for mosquitoes) has been studied.…”
Section: Discussionmentioning
confidence: 99%
“…An important extension of the model was proposed by Dietz et al [12] who added the inclusion of immunity. Thereafter, other extensive studies for malaria models have been carried out (see [3,19,21,22,29] and the references therein). Other studies concerning the effect of climatic changes and weather on malaria dynamics are shown in [13,23,24].…”
Section: Introductionmentioning
confidence: 99%